ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DONAT MENGGUNAKAN METODE FULL COSTING SEBAGAI PENENTUAN HARGA JUAL (STUDI KASUS DOYAN DONAT DI TEPI JALAN RAYA BEKUT) - Widia; Muhammad Farisan Luthfi; Novi Sentiya (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to determine the cost of production using the full costing method, compare it with MSME calculations, and set the selling price using the cost plus pricing method. This research was conducted at MSME Doyan Donat in Sambas, which has not implemented a comprehensive cost recording system. The results showed a difference of IDR 23,943,880 between MSMEs’ conventional calculation and the full costing method. Setting the selling price using the cost plus pricing method resulted in a price of IDR 2,308 per donut, while the MSME’s version was only IDR 1,192. This discrepancy of IDR 1,116 emphasizes the importance of applying cost accounting methods in strategic decision-making. This study concludes that the full costing and cost plus pricing methods significantly contribute to helping MSMEs set rational and profitable selling prices.